Characterization of the Causal Agent of Stem Canker of Soybean in Uruguay - Stewart, Silvina (Agrociencia Uruguay, 2015)
Sixty isolates of fungi belonging to the Diaporthe/Phomopsis complex in soybean were characterized using classical morpho-logy and PCR-RFLP to determine species and varieties within the species. Some of the morphological attributes studied were associated to certain variety within the complex Diaporthe/Phomopsis. Using PCR-RFLP, 37 isolates were identified as Diaporthe phaseolorum var. sojae, 19 as D. p. var. caulivora, and 4 as D. p. var. meridionalis. Despite the fact that both varieties of Diaporthe phaseolorum causing stem canker coexist in our country, 83 % of the isolates were identified as D. p. var. caulivora. This predominance has direct implications on disease management, since resistant genes incorporated in most available soybean cultivars to control stem canker are not effective against this variety of the fungus.